RHETORIC IN NEWS ARTICLES OF TVRI BROADCAST OF ‘KALTIM THIS WEEK’ - Yesi Herlina; Teguh Budiharso; Maria Teodora Ping (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
This study reported rhetorical style used in a news article to broadcast in TV RI of Kaltim This Week, specifying three kinds of styles: climax, cause, and effect.  This study used content analysis, identifying 10 articles available in the broadcast services.  The study revealed that three parts of rhetorical organization of news writing for broadcasting: climax part, cause part, and effect part were present in the news articles of Kaltim This Week. Climax parts appeared at the beginning of the writing. Irrelevant climax part happened as the editor put his/her subjective conclusion toward the story. The cause parts giving reasons and supporting facts were found in the middle of news articles. The absence of cause part was because the editor explained detailed information so he/she became unfocused to the reason. The effect parts were well presented in the news articles.